Vancomycin-resistant Enterococcus faecium: a national wide genomic snapshot in Switzerland - Dominique S. Blanc; Florian Mauffrey; Andrea C. Büchler; Danielle Vuichard-Gysin; Vanja Piezzi; Céline Gardiol; Marc Garcia; Trestan Pillonel; Laurent Poirel; Patrice Nordmann; Pascal Schlaepfer; Claudio Neidhöfer; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Performance evaluation of the BioFire respiratory panel 2.1 plus and exploratory analysis of Ct values for respiratory pathogen quantification - Alessandra Vitale; Ziggy Mahler; Valentin Loup; Zahera Dance; Gilbert Greub; Onya Opota (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Optimized detection of ESBL producers, carbapenemase producers, and VRE from rectal swabs using enrichment broth for superior screening sensitivity - Dominique S Blanc; Massiha Kamyar; Patrice Nordmann; Laurent Poirel; Gilbert Greub (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
This study evaluates the added value of using enrichment broths for improving the detection of multidrug-resistant (MDR) bacteria—VRE, ESBL producers, and carbapenemase-producing organisms (CPOs)—from rectal swabs. Comparing direct plating to enrichment-based methods significantly increased detection sensitivity, especially for CPOs (from 17 to 27 cases, a 58.8% increase). Detection rates for ESBL producers and VRE also improved significantly (by 20%). Pre-enrichment is therefore a valuable addition to routine MDR bacteria screening protocols, which is particularly useful when high accuracy is needed for prevention and infection control as well as for outbreak management.

A European survey on anaerobes from paediatric blood cultures: a comparative analysis with adults - Matteo Boattini; Arianna Aceti; Paulo Bastos; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Vasileios Kakouris; Yordan Kalchev; Ana Budimir; Branka Bedenić; Zana Rubic; Monica Licker; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Impact of rapid identification by MALDI-TOF MS from positive blood cultures in Enterococcus spp. bloodstream infections - Diogo Lopes; Bruno Grandbastien; Christina Orasch; Gilbert Greub; Antony Croxatto; Guy Prod’Hom; Benoit Guery (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Purpose Regarding bloodstream infections (BSI) Enterococcus spp. rank among the top five most common organisms. Due to enterococci intrinsic resistance, empiric antibiotic therapy is often inappropriate and early identification becomes crucial. Our objective was to assess the clinical impact of MALDI-TOF identification directly from positive blood cultures (BC) in Enterococcus spp. BSI (E-BSI). Methods A retrospective cohort study included all adult patients with E-BSI from 2010 to 2017 in a tertiary hospital. ID consultation within 48 h and MALDI-TOF identification directly from BC within 24 h were inclusion criteria. The primary outcome was antimicrobial treatment change following MALDI-TOF and secondary outcomes included 30-day and 1-year mortality, length of stay (LOS) and antimicrobial de-escalation. Results Among 267 BSI episodes, E. faecalis was isolated in 130 episodes (48.7%), E. faecium in 122 (45.7%), and 104 (39%) were polymicrobial. Empiric antibiotic therapy was inappropriate in 60.3% of patients. The LOS was 36 (IQR 20–64) days, 30-day and 1-year mortality were 16.1% and 43.4%, respectively. Enterococci identification with MALDI-TOF at the species level was possible in 66.3% cases and in 73% of monomicrobial cases. Antibiotics were changed in 85.3% of the former vs. 63.3% in remaining patients ( p < 10 − 4 ), and de-escalation occurred in 35% of subjects (vs. 12.2%, p = 10 − 4 ). Changing antibiotics after correct identification was associated with a shorter LOS. In multivariate analysis, appropriate antibiotic therapy before MALDI-TOF was protective against 30-day mortality (aOR 0.40(0.08–1.96)), and appropriate antibiotic therapy afterwards against 1-year mortality (aOR 0.21(0.05–0.84)). Conclusion In E-BSI, direct MALDI-TOF identification from positive BC has a significant clinical impact due to a more frequent antibiotic spectrum correction and de-escalation. This may improve patient outcomes, reducing LOS and potentially mortality. Clinical trial number Not applicable.

Correction to: Added diagnostic value of 16S rRNA gene pan-mycobacterial PCR for nontuberculous mycobacterial infections: a 10-year retrospective study - Simon Andenmatten; Onya Opota; Jessica Mazza-Stalder; Laurent Nicod; Gilbert Greub; Katia Jaton (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Core genome multilocus sequence typing of Clostridioides difficile to investigate transmission in the hospital setting - Paraskevas Filippidis; Laurence Senn; Fabrice Poncet; Bruno Grandbastien; Guy Prod’hom; Gilbert Greub; Benoit Guery; Dominique S. Blanc (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
Purpose Traditional epidemiological investigations of healthcare-associated Clostridioides difficile infection (HA-CDI) are often insufficient. This study aimed to evaluate a procedure that includes secondary isolation and genomic typing of single toxigenic colonies using core genome multilocus sequence typing (cgMLST) for the investigation of C. difficile transmission. Methods We analyzed retrospectively all toxigenic C. difficile -positive stool samples stored at the Lausanne University Hospital over 6 consecutive months. All isolates were initially typed and classified using a modified double-locus sequence typing (DLST) method. Genome comparison of isolates with the same DLST and clustering were subsequently performed using cgMLST. The electronic administrative records of patients with CDI were investigated for spatiotemporal epidemiological links supporting hospital transmission. A comparative descriptive analysis between genomic and epidemiological data was then performed. Results From January to June 2021, 86 C. difficile isolates were recovered from thawed samples of 71 patients. Thirteen different DLST types were shared by > 1 patient, and 13 were observed in single patients. A genomic cluster was defined as a set of isolates from different patients with ≤ 3 locus differences, determined by cgMLST. Seven genomic clusters were identified, among which plausible epidemiological links were identified in only 4/7 clusters. Conclusion Among clusters determined by cgMLST analysis, roughly 40% included unexplained HA-CDI acquisitions, which may be explained by unidentified epidemiological links, asymptomatic colonization, and/or shared common community reservoirs. The use of DLST, followed by whole genome sequencing analysis, is a promising and cost-effective stepwise approach for the investigation of CDI transmission in the hospital setting.

Added diagnostic value of 16S rRNA gene pan-mycobacterial PCR for nontuberculous mycobacterial infections: a 10-year retrospective study - Simon Andenmatten; Onya Opota; Jessica Mazza-Stalder; Laurent Nicod; Gilbert Greub; Katia Jaton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)
The diagnosis of mycobacterial infections has been dramatically improved by the introduction of molecular methods aimed to reduce the time to diagnosis as compared with culture. The broad range pan-mycobacterial PCR can detect all the mycobacterial species directly from clinical specimens. We aimed to evaluate its usefulness and its clinical added value for the diagnosis of nontuberculous mycobacterial (NTM) infections. We performed a retrospective study (2003–2013) including 952 samples taken from 639 patients with clinical suspicion of NTM infection. The performance of smear microscopy, PCR and culture was established using clinical data to investigate discrepant results. We also compared the time to microbial diagnosis between the direct PCR and culture. The sensitivity, specificity, positive and negative predictive values of the PCR were 61.6% (53.5–69.1), 99.1% (98.2–99.6), 92.8% (85.8–96.5) and 93.4% (91.6–94.9), respectively, when considering all specimens. When considering smear-positive specimens and smear-negative specimens, the sensitivity was 81.6% and 40%, respectively. The sensitivity for pulmonary and extra-pulmonary smear-positive specimens was 85.2% versus 72.7%. The median time to identification at species level was 35 days (SD, 17.67) for culture and 6 days (SD, 2.67) for the PCR (when positive), which represents a 29-day shorter time to results ( p < 0.0001). The 16S rRNA gene pan-mycobacterial PCR displays a substantial benefit in terms of time to diagnose NTM infections when compared with culture. Despite an excellent specificity, its sensitivity is yet limited in particular for smear-negative specimens, which might be improved by relying onto real-time PCRs.

Whole-genome sequencing revealed independent emergence of vancomycin-resistant Enterococcus faecium causing sequential outbreaks over 3 years in a tertiary care hospital - Mohamed H. H. Abdelbary; Laurence Senn; Gilbert Greub; Gregory Chaillou; Estelle Moulin; Dominique S. Blanc (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Cedratvirus lausannensis – digging into Pithoviridae diversity - Claire Bertelli; Linda Mueller; Vincent Thomas; Trestan Pillonel; Nicolas Jacquier; Gilbert Greub (Environmental Microbiology, 2017)
Summary Amoeba‐infecting viruses have raised scientists’ interest due to their novel particle morphologies, their large genome size and their genomic content challenging previously established dogma. We report here the discovery and the characterization of Cedratvirus lausannensis , a novel member of the Megavirales , with a 0.75–1 µm long amphora‐shaped particle closed by two striped plugs. Among numerous host cell types tested, the virus replicates only in Acanthamoeba castellanii leading to host cell lysis within 24 h. C. lausannensis was resistant to ethanol, hydrogen peroxide and heating treatments. Like 30 000‐year‐old Pithovirus sibericum , C. lausannensis enters by phagocytosis, releases its genetic content by fusion of the internal membrane with the inclusion membrane and replicates in intracytoplasmic viral factories. The genome encodes 643 proteins that confirmed the grouping of C. lausannensis with Cedratvirus A11 as phylogenetically distant members of the family Pithoviridae . The 575,161 bp AT‐rich genome is essentially devoid of the numerous repeats harbored by Pithovirus, suggesting that these non‐coding repetitions might be due to a selfish element rather than particular characteristics of the Pithoviridae family. The discovery of C. lausannensis confirms the contemporary worldwide distribution of Pithoviridae members and the characterization of its genome paves the way to better understand their evolution.

Culture‐independent genomics of a novel chlamydial pathogen of fish provides new insight into host‐specific adaptations utilized by these intracellular bacteria - Alyce Taylor‐Brown; Trestan Pillonel; Andrew Bridle; Weihong Qi; Nathan L. Bachmann; Terrence L. Miller; Gilbert Greub; Barbara Nowak; Helena M.B. Seth‐Smith; Lloyd Vaughan; Adam Polkinghorne (Environmental Microbiology, 2017)
Summary Several Chlamydiales families are associated with epitheliocystis, a common condition of the fish gill epithelium. These families share common ancestors with the Chlamydiaceae and environmental Chlamydiae . Due to the lack of culture systems, little is known about the biology of these chlamydial fish pathogens. We investigated epitheliocystis in cultured Orange‐spotted grouper ( Epinephelus coioides ) from North Queensland, Australia. Basophilic inclusions were present in the gills of 22/31 fish and the presence of the chlamydial pathogen in the cysts was confirmed by in situ hybridization. Giant grouper ( Epinephelus lanceolatus ) cultured in the same systems were epitheliocystis free. 16S rRNA gene sequencing revealed a novel member of the Candidatus Parilichlamydiaceae: Ca . Similichlamydia epinephelii. Using metagenomic approaches, we obtained an estimated 68% of the chlamydial genome, revealing that this novel chlamydial pathogen shares a number of key pathogenic hallmarks with the Chlamydiaceae , including an intact Type III Secretion system and several chlamydial virulence factors. This provides additional evidence that these pathogenic mechanisms were acquired early in the evolution of this unique bacterial phylum. The identification and genomic characterization of Ca . S. epinephelii provides new opportunities to study the biology of distantly‐related chlamydial pathogens while shining a new light on the evolution of pathogenicity of the Chlamydiaceae .

Comparative genome analysis of P seudomonas knackmussii B 13, the first bacterium known to degrade chloroaromatic compounds - Ryo Miyazaki; Claire Bertelli; Paola Benaglio; Jonas Canton; Nicoló De Coi; Walid H. Gharib; Bebeka Gjoksi; Alexander Goesmann; Gilbert Greub; Keith Harshman; Burkhard Linke; Josip Mikulic; et al. (Environmental Microbiology, 2015)
Summary P seudomonas knackmussii B 13 was the first strain to be isolated in 1974 that could degrade chlorinated aromatic hydrocarbons. This discovery was the prologue for subsequent characterization of numerous bacterial metabolic pathways, for genetic and biochemical studies, and which spurred ideas for pollutant bioremediation. In this study, we determined the complete genome sequence of B 13 using next generation sequencing technologies and optical mapping. Genome annotation indicated that B 13 has a variety of metabolic pathways for degrading monoaromatic hydrocarbons including chlorobenzoate, aminophenol, anthranilate and hydroxyquinol, but not polyaromatic compounds. Comparative genome analysis revealed that B 13 is closest to P seudomonas denitrificans and P seudomonas aeruginosa . The B 13 genome contains at least eight genomic islands [prophages and integrative conjugative elements ( ICEs )], which were absent in closely related pseudomonads. We confirm that two ICEs are identical copies of the 103 kb self‐transmissible element ICE clc that carries the genes for chlorocatechol metabolism. Comparison of ICE clc showed that it is composed of a variable and a ‘core’ region, which is very conserved among proteobacterial genomes, suggesting a widely distributed family of so far uncharacterized ICE . Resequencing of two spontaneous B 13 mutants revealed a number of single nucleotide substitutions, as well as excision of a large 220 kb region and a prophage that drastically change the host metabolic capacity and survivability.

Crescent and star shapes of members of the Chlamydiales order: impact of fixative methods - Brigida Rusconi; Julia Lienard; Sébastien Aeby; Antony Croxatto; Claire Bertelli; Gilbert Greub (Antonie van Leeuwenhoek, 2013)

Lausannevirus, a giant amoebal virus encoding histone doublets - Vincent Thomas; Claire Bertelli; François Collyn; Nicola Casson; Amalio Telenti; Alexander Goesmann; Antony Croxatto; Gilbert Greub (Environmental Microbiology, 2011)
Summary Large viruses infecting algae or amoebae belong to the NucleoCytoplasmic Large DNA Viruses (NCLDV) and present genotypic and phenotypic characteristics that have raised major interest among microbiologists. Here, we describe a new large virus discovered in Acanthamoeba castellanii co‐culture of an environmental sample. The virus, referred to as Lausannevirus, has a very limited host range, infecting Acanthamoeba spp. but being unable to infect other amoebae and mammalian cell lines tested. Within A. castellanii , this icosahedral virus of about 200 nm exhibits a development cycle similar to Mimivirus, with an eclipse phase 2 h post infection and a logarithmic growth leading to amoebal lysis in less than 24 h. The 346 kb Lausannevirus genome presents similarities with the recently described Marseillevirus, sharing 89% of genes, and thus belongs to the same family as confirmed by core gene phylogeny. Interestingly, Lausannevirus and Marseillevirus genomes both encode three proteins with predicted histone folds, including two histone doublets, that present similarities to eukaryotic and archaeal histones. The discovery of Lausannevirus and the analysis of its genome provide some insight in the evolution of these large amoebae‐infecting viruses.

Novel Chlamydiales strains isolated from a water treatment plant - Daniele Corsaro; Veronica Feroldi; Gemma Saucedo; Ferran Ribas; Jean‐François Loret; Gilbert Greub (Environmental Microbiology, 2009)
Summary Chlamydiae are obligate intracellular bacteria infecting free‐living amoebae, vertebrates and some invertebrates. Novel members are regularly discovered, and there is accumulating evidence supporting a very important diversity of chlamydiae in the environment. In this study, we investigated the presence of chlamydiae in a drinking water treatment plant. Samples were used to inoculate Acanthamoeba monolayers ( Acanthamoeba co‐culture), and to recover autochthonous amoebae onto non‐nutritive agar. Chlamydiae were searched for by a pan‐chlamydia 16S rRNA gene PCR from both Acanthamoeba co‐cultures and autochthonous amoebae, and phylotypes determined by 16S rRNA gene sequencing. Autochthonous amoebae also were identified by 18S rRNA gene amplification and sequencing. From a total of 79 samples, we recovered eight chlamydial strains by Acanthamoeba co‐culture, but only one of 28 amoebae harboured a chlamydia. Sequencing results and phylogenetic analysis showed our strains belonging to four distinct chlamydial lineages. Four strains, including the strain recovered within its natural host, belonged to the Parachlamydiaceae ; two closely related strains belonged to the Criblamydiaceae ; two distinct strains clustered with Rhabdochlamydia spp.; one strain clustered only with uncultured environmental clones. Our results confirmed the usefulness of amoeba co‐culture to recover novel chlamydial strains from complex samples and demonstrated the huge diversity of chlamydiae in the environment, by identifying several new species including one representing the first strain of a new family.

Biodiversity of amoebae and amoebae‐resisting bacteria in a drinking water treatment plant - Vincent Thomas; Jean‐François Loret; Michel Jousset; Gilbert Greub (Environmental Microbiology, 2008)
Summary The complex ecology of free‐living amoebae (FLA) and their role in spreading pathogenic microorganisms through water systems have recently raised considerable interest. In this study, we investigated the presence of FLA and amoebae‐resisting bacteria (ARB) at various stages of a drinking water plant fed with river water. We isolated various amoebal species from the river and from several points within the plant, mostly at early steps of water treatment. Echinamoeba ‐ and Hartmannella ‐related amoebae were mainly recovered in the drinking water plant whereas Acanthamoeba ‐ and Naegleria ‐related amoebae were recovered from the river water and the sand filtration units. Some FLA isolates were recovered immediately after the ozonation step, thus suggesting resistance of these microorganisms to this disinfection procedure. A bacterial isolate related to Mycobacterium mucogenicum was recovered from an Echinamoeba ‐related amoeba isolated from ozone‐treated water. Various other ARB were recovered using co‐culture with axenic Acanthamoeba castellanii , including mycobacteria, legionella, Chlamydia ‐like organisms and various proteobacteria. Noteworthy, a new Parachlamydia acanthamoebae strain was recovered from river water and from granular activated carbon (GAC) biofilm. As amoebae mainly multiply in sand and GAC filters, optimization of filter backwash procedures probably offers a possibility to better control these protists and the risk associated with their intracellular hosts.

Criblamydia sequanensis , a new intracellular Chlamydiales isolated from Seine river water using amoebal co‐culture - Vincent Thomas; Nicola Casson; Gilbert Greub (Environmental Microbiology, 2006)
Summary Accumulating evidence supports a role for Chlamydia ‐related organisms as emerging pathogens for human and animals. Assessment of their pathogenicity requires strain availability, at least for animal models and serological studies. As these obligate intracellular species are able to grow inside amoebae, we used co‐culture with Acanthamoeba castellanii in an attempt to recover new Chlamydia ‐related species from river water. We isolated two strains from eight water samples. The first strain is a new Parachlamydia acanthamoebae strain that differs from previously described isolates by only two bases in the complete 16S rRNA gene sequence. The second isolate is the first representative of a new Chlamydiales family, as demonstrated by genetic and phylogenetic analyses of the 16S rRNA, 23S rRNA, ADP/ATP translocase and RnpB encoding genes. Using fluorescent in situ hybridization and electron microscopy, we demonstrated that it grows in high numbers in amoebae, where it exhibits a Chlamydia ‐like developmental cycle with reticulate bodies and star‐like elementary bodies. Based on these results, we propose to name this new species ‘ Criblamydia sequanensis ’. This work confirmed that amoebal co‐culture is a relevant method to isolate new chlamydiae, and that it can be successfully applied to ecosystems colonized with a complex microbial community.

Absence of anti-hepatitis B surface antibody after vaccination does not necessarily mean absence of immune response - Gilbert Greub; Frédéric Zysset; Blaise Genton; François Spertini; Philippe C. Frei (Medical Microbiology and Immunology, 2001)